Membina Hubungan Harmonis Dalam Keluarga Melalui Komunikasi Efektif - Jasintha, Maria; Pranawukir, Iswahyu (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
The topic of community service is ‘Fostering the harmonious relationships amongst member of family’ by utilising effective communication approach. This program was warmly welcomed by the member of women’s PKK organisation of Jatipadang, Pasar Minggu, Jakarta. Keeping harmonious family relationships in a household has been challenging lately. The lack of effective communication amongst member of family occur in conjuction with the rapid development of technology and digital era. A family is indeed the basic foundation of community in social life. This activity is conducted temporarily. The people in charge of this program delivered the presentation which was interspersed with sharing experiences and followed by questions and answers sessions.This activity was conducted in an informal setting. The participants followed it eagerly and enthusiastically and willing to share their experiences in their households. The people in charge of this program realised that this activity could have been more effective and successful if men (their husbands) joined the discussions. Due to their difficulty in finding the right time, this activity therefore was only attended by the women. The driving factor of this activity was indeed the women’s member of PKK in Jatipadang, Pasar Minggu, who concerned about the changing relations among the members in their households. The limitation of time provided and the typical mom’s busy schedule settings are of two obstacles to make this program more successful. The diversity of their cultural and educational backgrounds has also contributed to the nature of this program delivered